Speech and music perception with the new fine structure speech coding strategy: preliminary results - Arnoldner, Christoph; Riss, Dominik; Brunner, Markus; Durisin, Martin; Baumgartner, Wolf-Dieter; Hamzavi, >Jafar-Sasan (Acta oto-laryngologica, 2007)
Conclusions. Taking into account the excellent results with significant improvements in the speech tests and the very high satisfaction of the patients using the new strategy, this first implementation of a fine structure strategy could offer a new quality of hearing with cochlear implants (CIs). Objective. This study consisted of an intra-individual comparison of speech recognition, music perception and patient preference when subjects used two different speech coding strategies with a MedEl Pulsar CI: continuous interleaved sampling (CIS) and the new fine structure processing (FSP) strategy. In contrast to envelope-based strategies, the FSP strategy also delivers subtle pitch and timing differences of sound to the user and is thereby supposed to enhance speech perception in noise and increase the quality of music perception. Patients and methods. This was a prospective study assessing performance with two different speech coding strategies. The setting was a CI programme at an academic tertiary referral centre. Fourteen post-lingually deaf patients using a MedEl Pulsar CI with a mean CI experience of 0.98 years were supplied with the new FSP speech coding strategy. Subjects consecutively used the two different speech coding strategies. Speech and music tests were performed with the previously fitted CIS strategy, immediately after fitting with the new FSP strategy and 4, 8 and 12 weeks later. The main outcome measures were individual performance and subjective assessment of two different speech processors. Results. Speech and music test scores improved statistically significantly after conversion from CIS to FSP strategy. Twelve of 14 patients preferred the new FSP speech processing strategy over the CIS strategy.